Single-cell metabolite profiling of stalk and glandular cells of intact trichomes with internal electrode capillary pressure probe electrospray ionization mass spectrometry - Nakashima, Taiken (2016)
In this report, we developed the pressure probe electrospray ionization-mass spectrometry with internal electrode capillary (IEC-PPESI-MS) which enables high spatial-resolution cell sampling, precise postsampling manipulation, and high detection sensitivity. Using this technique, a comparative in situ single-cell metabolite profiling of stalk and glandular cells, the two adjacent cell types comprising a trichome unit in tomato plants (Solanum lycopersicum L.), were performed to clarify the extent of metabolic differentiation between two cell types as well as among different types of trichomes. Owing to high sensitivity of the system, less than a picoliter cell sap from a single stalk cell sufficiently yielded a number of peaks of amino acids, organic acids, carbohydrates, and flavonoids. The minimal cell sap removal from a stalk cell without severe disturbance of trichome structure enabled sequential analysis of adjacent glandular cell on the same trichome, which showed the presence of striking differences in metabolite compositions between two adjacent cell types. Comparison among different types of trichome also revealed significant variations in metabolite profiles, particularly in flavonoids and acyl sugars compositions. Some metabolites were found only in specific cell types or particular trichome types. Although extensive metabolomics analysis of glandular cells of tomato trichomes has been previously documented, this is the first report describing cell-to-cell variations in metabolite compositions of stalk and glandular cells as well as in different trichome types. Further application of this technique may provide new insights into distinct metabolism in plant cells displaying variations in shape, size, function and physicochemical properties.